Incorrect porque no sabes cómo hacerlo solo hazlo y ya!!
Answer:
x = -11
Step-by-step explanation:
2x + 23 + 9 = x + 21
Combine common factors
2x + 32 = x + 21
Subtract x from both sides
x + 32 = 21
Subtract 32 from both sides
x = -11
Use inverse operations and subtract 3 from 9 which is -12 then divide -12 by 6 which is -2
-9=3+6x
-3 -3
-12=6x
-12/6=6x/6
-2=x
Answer:
49,820
Step-by-step explanation:
so what you were going to do first is you're going to do 940 * 53 there is which equals 2820 and then you're going to do turtle messes so then you're going to do 5 * 0 which equals zero then five times for which equals 20 + 5 * 9 which equals 45 + 2 which 45 + 2 equals 47 so you have 2820 + 47000 which equals 49,820